Synthesis and Characterization of a Ni(II) and Cu(I) Complexes of Schiff Base Derived from Salicylaldehyde - DEMIRHAN, NEBAHAT; KESER KARAOGLAN, GULNUR; AYDIN, SEZGIN (Asian Journal of Chemistry, 2010)
A new Schiff-base ligand, 2-(3-[2-(6-aminoquino[8,7-b]azin-5- yliminomethyl) phenoxy]propoxy)-benzaldehyde has been synthesized from the reaction of l,5-bis(2'-formylphenyl)-l,5-dioxapentane with 5,6- diamino-l,10-phenanthroline and its metal complexes with Cu(I) and Ni(II) have been prepared. Molecular structure of Schiff-base and its metal complexes have been investigated and characterized by FT-IR, 1H NMR, 13C NMR, fluorescence, FAB (+) mass spectra, elemental analysis, magnetic measurements and TGA-DSC-DTG techniques.